COMPOSITE STOCK PRICE INDEX (IHSG) MACRO FACTOR IN INVESTMENT IN STOCK (EQUITY FUNDS) - Andi Desfiandi; Abshor Marantika (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Investors often find it difficult to valuate andpurchase stocks with good performance that provideoptimum yields. Inadequate information regarding how tomake good investments is one of the main reasons whypeople lose interest to invest in capital market. Thepurpose of this research is to find a stock performancemeasurement model by using accounting and financialmanagement system that is made by using the informationfrom stocks turnover ratio and risk level of stocks. Thisperformance measurement model can be an important toolfor investors to identify the stock performance factor.Therefore, investors can valuate and purchase stocks withoptimum performance and yields.US Dollar (USD)/ Indonesian Rupiah (IDR) ratehas significantly negative influence on IndonesianComposite Price Index (IHSG) movement since adepreciation of IDR discourages investors to invest inIndonesia Stock Exchange (IDX). Therefore, the investorsdivert their investments from stock market to foreignexchange market to arbitrage. Straits Times Index (STI)has significantly positive influence on IHSG sinceSingapore and Indonesia share common investors thatcauses the movement of STI is followed by the movementof IHSG.KEYWORDS: Performance, Mutual Funds, Risk Stock.